Investigation of bacterial inactivation in apheresis platelets with 24 or 30 hours between inoculation and inactivation. Issue 3 (17th May 2016) - Wagner, S. J.; Benjamin, R. J.; Hapip, C. A.; Kaelber, N. S.; Turgeon, A. M.; Skripchenko, A.; Stassinopoulos, A.
Abstract : Background and Objectives: Blood Centre logistics, staffing and donor scheduling may be optimized if pathogen inactivation (PI) of platelets can be delayed until Day 1, but bacteria may rapidly grow during this time. This study evaluates bacterial PI performed 24 and 30 h after collection. Materials and Methods: PAS‐3 platelet units were collected on the Amicus and subsequently inoculated (3–53 CFU/unit) with 1of 5 transfusion relevant bacterial species ( n = 3/organism). Units were then stored for either 24 ± 0·3 or 30 ± 0·3 h at 20–24°C with agitation, subsequently treated with amotosalen and UVA, and stored for 7 days. Samples were taken before and after inactivation, on Days 2, 5 and 7 for BacT/ALERT testing, and on Days 5 and 7 for plate counts. Results: All samples from units taken prior to inactivation either demonstrated positive plate culture counts, or, in untreated positive controls, were culture‐positive during storage. All contaminated units treated with amotosalen and UVA 24 after inoculation were culture‐negative on all days tested. With inactivation performed 30 h following inoculation, one of 15 units (1‐of‐3 replicates) was culture‐positive with Klebsiella pneumonia (1 × 10 9 CFU/ml) by Day 5. Conclusion: Photochemical treatment did not inactivate 1 of 15 units to sterility in apheresis platelets stored in PAS with a 30‐h delay between contamination and treatment, but did inactivate 15 of 15 units with a 24‐h delay.